Hybrid skeleton wave-absorbing aerogel wrapped by multi-walled carbon nanotubes and preparation method of hybrid skeleton wave-absorbing aerogel
By using a titanium carbide/aramid nanofiber hybrid skeleton structure wrapped with multi-walled carbon nanotubes, the deficiencies of existing aerogels in terms of mechanical properties, wave-absorbing properties and hydrophobic properties are solved, achieving higher performance and more Low production costs promote the widespread use of aerogels in future sustainable development and applications.
Patent Information
- Application Number
- CN202411601236.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing aerogels have shortcomings in mechanical properties, wave absorption properties, hydrophobic properties and production costs, which limit their widespread use in future sustainable development and applications.
The hybrid skeleton suction air gel with a multi -wall carbon nanot barrel is stirred and centrifuged by mixing MXENE, lithium fluoride, and hydrochloric acid in a specific proportion to prepare MXENE decentralized liquid and mix with the aramal nano fiber gel. Dry treatment, eventually impregnated in the decentralized liquid of carbon tube to form a multi -wall carbon nanotuba wrapped in titanium/aramite nano -fiber hybrid suction gas gel.
It significantly improves the extreme temperature resistance of gas gel, the conductivity, the opposite sex, sensing performance, and EMI shielding performance of the gas gel, enhance their strength and toughness, improve the stability of hydration, and reduce production costs.
Smart Images

Figure CN119350701A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the cross-technical field of porous materials and high molecular polymers, in particular to a hybrid skeleton wave-absorbing aerogel wrapped by multi-walled carbon nanotubes and a preparation method thereof. Background Art
[0002] Aerogel is a solid material with a nanoporous network structure and filled with gaseous dispersion medium in the pores. It is considered to be the lightest solid in the world and is known as "solidified smoke". This material was first invented in the 1930s and has been a hot topic of research for nearly ninety years. Due to its extremely light weight, high-efficiency thermal insulation performance and nanoporous network structure, it exhibits excellent physical properties in many fields such as acoustics, optics, electricity and mechanics, and is widely used in many fields due to its unique heat-resistance principle and diverse material types. With the development of science and technology and the promotion of the dual-carbon policy, energy conservation has become the main theme of the future development of the chemical, energy and construction industries. As an efficient and energy-saving thermal insulation material, the industry demand for aerogel is expected to increase rapidly. Aerogel performs better than traditional thermal insulation materials in terms of thermal insulation, service life, waterproofness and flame retardancy, showing great application prospects.
[0003] Currently, the mainstream aerogel is silica aerogel, which has good thermal insulation and adsorption evolution functions. Its preparation process is a combination of sol-gel method and supercritical drying, but it has poor mechanical properties, low wave absorption performance, unstable hydrophobic properties, high production equipment requirements, high cost, and difficulty in mass production. These problems limit the sustainable development and application of aerogel in the future. Summary of the invention
[0004] In view of the problems in the prior art, the present invention provides a hybrid skeleton absorbing aerogel wrapped with multi-walled carbon nanotubes and a preparation method thereof.
[0005] The present invention is achieved through the following technical solutions: A hybrid skeleton absorbing aerogel wrapped with multi-walled carbon nanotubes comprises the following steps: S1, stirring and centrifuging MXene, lithium fluoride and hydrochloric acid in a ratio of (2-3) g: (3-4) g: (50-60) mL to prepare a MXene dispersion; S2, uniformly mixing 5-10 mL of MXene dispersion with 50-60 g of aramid nanofiber gel to obtain a mixed gel; S3, using a mold to form a thin layer of gel from the mixed gel, first freezing it, and then freeze-drying it for the first time to obtain an aerogel; S4, immersing the aerogel in a carbon tube dispersion, then performing a second freezing, and then performing a second freeze drying to obtain a titanium carbide / aramid nanofiber hybrid microwave absorbing aerogel wrapped by multi-walled carbon nanotubes.
[0006] Preferably, in S1, stirring is performed in an oil bath at 45-50° C. for 40-48 h; and hydrochloric acid is supplemented 5 h before the end.
[0007] Preferably, in S1, after the stirring is completed, centrifugation is performed multiple times in an increasing centrifugal speed manner to obtain a MXene dispersion.
[0008] Preferably, in S2, the preparation method of the aramid nanofiber gel is: the ratio of alkali solution, dimethyl sulfoxide and para-aramid nanofiber is (2-3) mL: (500-600) mL: (1-2) g, and the reaction is carried out for 8-10 hours under the condition of stirring speed of (400-8000) r / min.
[0009] Preferably, S3, the thickness of the thin layer of gel is 2 to 5 mm.
[0010] Preferably, in S3, during the first freezing, the temperature is -(60-62)°C and the time is 10-12 hours.
[0011] Preferably, in S3, during the first freeze drying, the temperature is -(50-59)°C and the time is 24-48 hours.
[0012] Preferably, in S4, during the second freezing, the temperature is - (60 to 62) °C and the time is 10 to 12 hours.
[0013] Preferably, in S4, during the second freeze drying, the temperature is -(50-59)°C and the time is 12-24 hours.
[0014] A product obtained from the hybrid skeleton absorbing aerogel wrapped by multi-walled carbon nanotubes.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The hybrid skeleton absorbing aerogel wrapped with multi-walled carbon nanotubes of the present invention includes a MXene dispersion prepared by an etching reaction and a preparation of aramid nanofibers. Compared with the above-mentioned existing preparation technologies, the present application optimizes and limits the relevant performances, making it more conducive to combining the mechanical properties of aramid nanofibers and the conductive properties of MXene, and exhibiting remarkable characteristics in extreme temperature resistance, conductivity anisotropy, sensing performance and EMI shielding performance.
[0016] All aerogels in the present invention are in the form of thin layers, which is beneficial to solvent diffusion and gel formation in the shortest time on the one hand, and is beneficial to reducing freezing stress concentration and deformation on the other hand, and is beneficial to shortening freezing and drying time, providing convenience for production.
[0017] After the aerogel in the present invention is impregnated with the carbon tube dispersion, it is not dried in an oven, but freeze-dried by a freeze dryer. The freezing step can rapidly solidify the carbon tube dispersion in the pore structure of the aerogel, thereby maintaining the three-dimensional network structure of the aerogel in the subsequent drying process, and maintaining the integrity of the aerogel structure; and freeze drying (also known as freeze dehydration) is carried out at low temperatures, which can effectively avoid the shrinkage and deformation of the aerogel caused by water evaporation, so that the microporous aerogel can better highlight the grid structure.
[0018] In the present invention, MXene and aramid nanofibers are mixed to form a skeleton structure, which not only protects MXene and avoids oxidative decomposition due to direct contact with air, but also solves the problem that MXene alone is used to prepare aerogels, which has weak mechanical properties and cannot be directly applied. At the same time, extensive hydrogen bonds are formed between MXene and aramid nanofibers, which avoids MXene from damaging the stress transfer integrity of aramid nanofibers.
[0019] Titanium carbide has the characteristics of high hardness, good electrical conductivity and thermal conductivity, and can be used to manufacture high-strength knives, abrasives, electronic components and radiators. Aramid nanofibers have excellent properties such as high strength, high modulus, high temperature resistance and corrosion resistance, and are widely used in aerospace, transportation, electricity, national defense and military fields. After titanium carbide and aramid nanofibers are composited, the strength and toughness of aerogels can be effectively improved, and they have good electrical conductivity and electromagnetic loss capacity, and better absorption and attenuation effects on electromagnetic waves; at the same time, the hydrophobic stability of aerogels can be improved, so that they can maintain good hydrophobic properties under a wider range of temperature and humidity conditions. In the present invention, multi-walled carbon nanotubes are preferably used as wave absorbing enhancers, because multi-walled carbon nanotubes are lightweight and have strong electromagnetic wave loss capacity. In addition, the multi-walled carbon nanotubes are added to the aerogel through the impregnation process, which not only avoids further complex processes, but also constructs an interface with a microstructure "synapse", which is beneficial to the interweaving of the interface with the air and promotes the improvement of the impedance matching of electromagnetic waves. On the other hand, this complex microstructure is beneficial to the increase of the reflection probability of electromagnetic waves and increases the energy dissipation of electromagnetic waves. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a flow chart of a method for preparing a hybrid skeleton absorbing aerogel wrapped with multi-walled carbon nanotubes of the present invention; Figure 2 is a surface SEM image of the aerogel prepared in Example 1; Figure 3 This is an enlarged SEM image of the surface of the aerogel prepared in Example 1.
[0021] Figure 4 is a 3D graph of reflection loss of the aerogel of Example 1; Figure 5 This is a 3D graph of the reflection loss of the aerogel in Example 5. DETAILED DESCRIPTION The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0022] The present invention discloses a hybrid skeleton wave absorbing aerogel wrapped with multi-walled carbon nanotubes, referring to Figure 1 , including the following steps: S1, MXene, lithium fluoride and hydrochloric acid are stirred and centrifuged in a ratio of (2-3) g: (3-4) g: (50-60) mL to prepare a MXene dispersion; wherein the stirring is carried out in an oil bath at 45-50°C for 40-48 h; and hydrochloric acid is supplemented 5 h before the end. After the stirring is completed, the centrifugation is performed multiple times in an increasing centrifugal speed to obtain a MXene dispersion. Specifically, the first centrifugation is performed at a speed of 3500 r / min for five minutes, the second centrifugation is performed at a speed of 4000 r / min for 15 min, the supernatant is discarded, water is added and allowed to stand overnight. The third centrifugation is performed at a speed of 5000 r / min for 15 min, the fourth centrifugation is performed at a speed of 6000 r / min for 20 min, the supernatant is discarded, water is added and allowed to stand overnight. The fifth centrifugation is performed at a speed of 8000 r / min for 20 min, 10 ml of water is added, and it is allowed to stand overnight to obtain a MXene dispersion.
[0023] S2, 5-10 mL of MXene dispersion and 50-60 g of aramid nanofiber gel are uniformly mixed to obtain a mixed gel; wherein the preparation method of the aramid nanofiber gel is as follows: the ratio of alkali solution, dimethyl sulfoxide and para-aramid nanofiber is (2-3) mL: (500-600) mL: (1-2) g, and the reaction is carried out at a stirring speed of 400-8000 r / min for 8-10 h.
[0024] S3, the mixed gel is made into a thin layer of gel with a thickness of 2~5mm using a mold, first frozen in a refrigerator, and then freeze-dried for the first time to obtain aerogel; wherein, during the first freezing, the temperature is -(60~62)℃, the time is 10~12h; during the first freeze drying, the temperature is -(50~59)℃, and the time is 24~48h. The mold is not limited to any shape, and the mold, replacement solvent and replacement method are convenient and feasible. The mold is an ordinary plastic mold, the replacement solvent is deionized water, and the replacement method is static, which is mainly carried out through the principles of phase separation and molecular diffusion, which lays a good foundation for the industrialization of the technology of the present invention.
[0025] S4, immersing the aerogel in a carbon tube dispersion, then performing a second freezing, and then performing a second freeze drying to obtain a titanium carbide / aramid nanofiber hybrid microwave absorbing aerogel wrapped by multi-walled carbon nanotubes.
[0026] During the second freezing, the temperature is - (60 ~ 62) ° C, and the time is 10 ~ 12 hours; during the second freeze-drying, the temperature is - (50 ~ 59) ° C, and the time is 12 ~ 24 hours.
[0027] Example 1 Step 1: MXene, lithium fluoride and 0.37g / mL hydrochloric acid are added to the reactor in the ratio of 2g:3g:50mL, and reacted in an oil bath at 45°C at a stirring speed of 4000r / min for 48h, and 10mL of hydrochloric acid is added 5h before the end. After stirring, centrifuge at an increasing speed of 3500-8000 r / min for 20min each time, 7 times, to prepare a MXene dispersion.
[0028] Step 2: Evenly mix 5 mL of MXene dispersion with 52 g of para-aramid nanofiber gel.
[0029] Step 3: Place the uniformly mixed gel in a square plastic mold, scrape the surface flat, so that the thickness of the thin layer of gel after the aramid nanofiber gel mixed with the MXene dispersion is 3 mm after introduction and spreading, and put it in a refrigerator to freeze for 12 hours, and then put it in a freeze dryer with a freeze drying temperature of -52°C for freeze drying for 48 hours to obtain aerogel.
[0030] Step 4, cut the aerogel into small pieces, immerse them evenly in 2 mL (add 4 mL of water) of carbon tube dispersion for 5 minutes, put them in a refrigerator for 10 hours, and then put them in a freeze dryer at a freeze drying temperature of -52°C for 12 hours to obtain multi-walled carbon nanotube-wrapped titanium carbide / aramid nanofiber hybrid absorbing aerogel.
[0031] like Figure 2As shown, the hybrid skeleton absorbing aerogel structure wrapped by multi-walled carbon nanotubes is Figure 3 It can be clearly seen that freeze drying can quickly solidify the carbon tube dispersion in the pore structure of the aerogel to form a skeleton structure. Figure 4 It can be seen that the multi-walled carbon nanotube-wrapped titanium carbide / aramid nanofiber hybrid absorbing aerogel in this embodiment has a porosity of 98.32%, a thickness of 4.07 mm, a reflection loss of -36.94 dB, an effective absorption bandwidth of 2.275 GHz, and a uniform periodic structure.
[0032] Example 2 Step 1: Using the etching method, MXene, lithium fluoride and 0.37g / mL hydrochloric acid were added to the reactor in the ratio of 2g:3g:50mL, and reacted in an oil bath at 45°C at a stirring speed of 4000r / min for 48h, and 10mL of hydrochloric acid was added 5h before the end. After stirring, centrifugation was performed at an increasing speed of 3500-8000 r / min, each centrifugation was performed for 20min, and the number of times was 7 times to prepare a MXene dispersion.
[0033] Step 2: 6 mL of MXene dispersion was evenly mixed with 52 g of para-aramid nanofiber gel.
[0034] Step 3: Place the evenly mixed gel in a square plastic mold, scrape the surface flat, and make the thickness of the thin layer of gel after the aramid nanofiber gel mixed with the MXene dispersion is 3 mm after introduction and spreading. Put it in a refrigerator and freeze it for 12 hours. Then put it in a freeze dryer with a freeze drying temperature of -52°C and freeze dry it for 48 hours to obtain aerogel.
[0035] Step 4, cut the aerogel into small pieces, immerse them evenly in 2 mL (add 4 mL of water) of carbon tube dispersion for 5 minutes, put them in a refrigerator for 10 hours, and then put them in a freeze dryer at a freeze drying temperature of -52°C for 12 hours to obtain multi-walled carbon nanotube-wrapped titanium carbide / aramid nanofiber hybrid absorbing aerogel.
[0036] The multi-walled carbon nanotube-wrapped titanium carbide / aramid nanofiber hybrid absorbing aerogel in this embodiment has a porosity of 98.61%, a thickness of 3.73 mm, a reflection loss of -30.35 dB, an effective absorption bandwidth of 2.351 GHz, and a uniform periodic structure.
[0037] Example 3 Step 1: Using the etching method, MXene, lithium fluoride and 0.37g / mL hydrochloric acid were added to the reactor in the ratio of 2g:3g:50mL, and reacted in an oil bath at 45°C at a stirring speed of 4000r / min for 48h, and 10mL of hydrochloric acid was added 5h before the end. After stirring, centrifugation was performed at an increasing speed of 3500-8000 r / min, each centrifugation was performed for 20min, and the number of times was 7 times to prepare a MXene dispersion.
[0038] Step 2: Evenly mix 7 mL of MXene dispersion with 52 g of para-aramid nanofiber gel.
[0039] Step 3: Place the uniformly mixed gel in a square plastic mold, scrape the surface flat, so that the thickness of the thin layer of gel after the aramid nanofiber gel mixed with the MXene dispersion is 3 mm after introduction and spreading, and put it in a refrigerator to freeze for 12 hours, and then put it in a freeze dryer with a freeze drying temperature of -52°C for freeze drying for 48 hours to obtain aerogel.
[0040] Step 4, cut the aerogel into small pieces, immerse them evenly in 2 mL (add 4 mL of water) of carbon tube dispersion for 5 minutes, put them in a refrigerator for 10 hours, and then put them in a freeze dryer at a freeze drying temperature of -52°C for 12 hours to obtain multi-walled carbon nanotube-wrapped titanium carbide / aramid nanofiber hybrid absorbing aerogel.
[0041] The multi-walled carbon nanotube-wrapped titanium carbide / aramid nanofiber hybrid absorbing aerogel in this embodiment has a porosity of 98.75%, a thickness of 3.88 mm, a reflection loss of -24.66 dB, an effective absorption bandwidth of 2.572 GHz, and a uniform periodic structure.
[0042] Example 4 Step 1: Using the etching method, MXene, lithium fluoride and 0.37g / mL hydrochloric acid were added to the reactor in the ratio of 2g:3g:50mL, and reacted in an oil bath at 45°C at a stirring speed of 4000r / min for 48h, and 10mL of hydrochloric acid was added 5h before the end. After stirring, centrifugation was performed at an increasing speed of 3500-8000 r / min, each centrifugation was performed for 20min, and the number of times was 7 times to prepare a MXene dispersion.
[0043] Step 2: Evenly mix 8 mL of MXene dispersion with 52 g of para-aramid nanofiber gel.
[0044] Step 3: Place the uniformly mixed gel in a square plastic mold, scrape the surface flat, so that the thickness of the thin layer of gel after the aramid nanofiber gel mixed with the MXene dispersion is 3 mm after introduction and spreading, and put it in a refrigerator to freeze for 12 hours, and then put it in a freeze dryer with a freeze drying temperature of -52°C for freeze drying for 48 hours to obtain aerogel.
[0045] Step 4, cut the aerogel into small pieces, immerse them evenly in 2 mL (add 4 mL of water) of carbon tube dispersion for 5 minutes, put them in a refrigerator for 10 hours, and then put them in a freeze dryer at a freeze drying temperature of -52°C for 12 hours to obtain multi-walled carbon nanotube-wrapped titanium carbide / aramid nanofiber hybrid absorbing aerogel.
[0046] The multi-walled carbon nanotube-wrapped titanium carbide / aramid nanofiber hybrid absorbing aerogel in this embodiment has a porosity of 98.34%, a thickness of 4.12 mm, a reflection loss of -16.19 dB, an effective absorption bandwidth of 2.734 GHz, and a uniform periodic structure.
[0047] Example 5 Step 1: Using the etching method, MXene, lithium fluoride and 0.37g / mL hydrochloric acid were added to the reactor in the ratio of 2g:3g:50mL, and reacted in an oil bath at 45°C at a stirring speed of 4000r / min for 48h, and 10mL of hydrochloric acid was added 5h before the end. After stirring, centrifugation was performed at an increasing speed of 3500-8000 r / min, each centrifugation was performed for 20min, and the number of times was 7 times to prepare a MXene dispersion.
[0048] Step 2: Evenly mix 10 mL of MXene dispersion with 52 g of para-aramid nanofiber gel.
[0049] Step 3: Place the evenly mixed gel in a square plastic mold, scrape the surface flat, so that the thickness of the aramid nanofiber gel mixed with the MXene dispersion is 3 mm after introduction and spreading, and put it in a refrigerator for 12 hours, and then put it in a freeze dryer at a freeze drying temperature of -52°C for freeze drying for 48 hours to obtain aerogel.
[0050] Step 4, cut the aerogel into small pieces, immerse them evenly in 2 mL (add 4 mL of water) of carbon tube dispersion for 5 minutes, put them in a refrigerator for 10 hours, and then put them in a freeze dryer at a freeze drying temperature of -52°C for 12 hours to obtain multi-walled carbon nanotube-wrapped titanium carbide / aramid nanofiber hybrid absorbing aerogel.
[0051] Reference Figure 5The multi-walled carbon nanotube-wrapped titanium carbide / aramid nanofiber hybrid absorbing aerogel in this embodiment has a porosity of 99.06%, a thickness of 3.57 mm, a reflection loss of -13.23 dB, an effective absorption bandwidth of 2.975 GHz, and a uniform periodic structure; in addition, the process flow is stable, the operability is strong, the comprehensive cost is controllable, and it has good social value.
[0052] The invention also discloses a product obtained from the hybrid skeleton wave-absorbing aerogel wrapped by multi-walled carbon nanotubes.
[0053] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.
Claims
1. A method for preparing a hybrid skeleton absorbing aerogel wrapped with multi-walled carbon nanotubes, characterized in that: The following steps are involved: S1, stirring and centrifuging MXene, lithium fluoride and hydrochloric acid in a ratio of (2-3) g: (3-4) g: (50-60) mL to prepare a MXene dispersion; S2, uniformly mixing 5-10 mL of MXene dispersion with 50-60 g of aramid nanofiber gel to obtain a mixed gel; S3, using a mold to form a thin layer of gel from the mixed gel, first freezing it, and then freeze-drying it for the first time to obtain an aerogel; S4, immersing the aerogel in a carbon tube dispersion, then performing a second freezing, and then performing a second freeze drying to obtain a titanium carbide / aramid nanofiber hybrid microwave absorbing aerogel wrapped by multi-walled carbon nanotubes.
2. The method for preparing the hybrid skeleton absorbing aerogel wrapped by multi-walled carbon nanotubes according to claim 1, characterized in that: In S1, stirring is carried out in an oil bath at 45-50°C for 40-48 hours; hydrochloric acid is supplemented 5 hours before the end.
3. The method for preparing the hybrid skeleton absorbing aerogel wrapped by multi-walled carbon nanotubes according to claim 1, characterized in that: In S1, after the stirring is completed, centrifugation is performed multiple times in an increasing centrifugal speed to obtain a MXene dispersion.
4. The method for preparing a hybrid skeleton absorbing aerogel wrapped with multi-walled carbon nanotubes according to claim 1, characterized in that: In S2, the preparation method of aramid nanofiber gel is as follows: the ratio of alkali solution, dimethyl sulfoxide and para-aramid nanofiber is (2-3) mL: (500-600) mL: (1-2) g, and the reaction is carried out for 8-10 hours under the condition of stirring speed of 400-8000 r / min.
5. The method for preparing the hybrid skeleton absorbing aerogel wrapped by multi-walled carbon nanotubes according to claim 1, characterized in that: S3, the thickness of the thin layer of gel is 2~5mm.
6. The method for preparing hybrid skeleton absorbing aerogel wrapped by multi-walled carbon nanotubes according to claim 1, characterized in that: In S3, during the first freezing, the temperature is - (60 ~ 62) ℃ and the time is 10 ~ 12h.
7. The method for preparing hybrid skeleton absorbing aerogel wrapped by multi-walled carbon nanotubes according to claim 1, characterized in that: In S3, during the first freeze-drying, the temperature is - (50 ~ 59) ° C and the time is 24 ~ 48h.
8. The method for preparing hybrid skeleton absorbing aerogel wrapped by multi-walled carbon nanotubes according to claim 1, characterized in that: S4, during the second freezing, the temperature is - (60 ~ 62) ℃, and the time is 10 ~ 12h.
9. The method for preparing hybrid skeleton absorbing aerogel wrapped by multi-walled carbon nanotubes according to claim 1, characterized in that: In S4, during the second freeze drying, the temperature is - (50 ~ 59) ° C and the time is 12 ~ 24h.
10. A product obtained from the hybrid skeleton absorbing aerogel wrapped by multi-walled carbon nanotubes according to any one of claims 1 to 9.
Citation Information
Patent Citations
Aramid nanofiber / MXene composite conductive aerogel and preparation method thereof
CN111040238A
Preparation method of aerogel with electromagnetic shielding and sound absorption functions
CN114920978A
MXene-based aerogel, preparation method thereof and application of MXene-based aerogel in wave-absorbing material
CN117939870A
Cited By
Carbon / carbon composite aerogel based on congruent resin coating and preparation method
CN120479316A